Two New Diterpenoids from Biscogniauxia sp. and Their Activities - Zhao, Huan; Liu, Yue; Zhang, Meng; Chen, Guo-dong; Hu, Dan; Guo, Liang-dong; Zhao, Zhong-xiang; Zhi, Hui; Gao, Hao (Frontiers in Chemistry, 2021)
Two new diterpenoids, including a seco-isopimarane type (1) and an abietane type (2), were isolated from Biscogniauxia sp. (71-10-1-1). Their structures, including absolute configurations, were elucidated by NMR spectroscopic analyses, X-ray crystallography, 13C chemical shifts calculations, and ECD calculations. This is the first report of diterpenoids from Biscogniauxia sp. Furthermore, short-term memory enhancement against Alzheimer’s disease (AD), anti-inflammatory, and cytotoxic activities of 1−2 were also evaluated. The results showed that compound 1 exhibited short-term memory enhancement activity against AD.